The Aplication Of Restorative Justive To Fraud Cases In The Palangkaraya District Attorney’s Office - Akbar, Muhammad Athaillah; Sulastri, Indang; Dewi, Yurika Fahliany (Journal of Law, Politic and Humanities, 2025)
The purpose of this study is to explore the implementation and challenges of restorative justice in resolving fraud cases at the Palangkaraya District Prosecutor's Office. This research adopts an empirical legal method, involving fieldwork and interviews to gather data. The findings indicate that the application of restorative justice in fraud cases at the Palangkaraya District Prosecutor's Office reflects a shift from a repressive penal system toward a more recovery-oriented, reconciliatory, and socially responsible approach. However, its implementation remains limited to minor offenses and depends on voluntary restitution and mutual agreement. Of the 27 fraud cases recorded between 2023 and 2025, only two were resolved through restorative justice, highlighting the need for a thorough evaluation to broaden and optimize its application.